The Manifestor Prophecy - Thomas, Angie (UK, 2023)
Nic Blake is a Manifestor. All she wants is to learn the Gift, so she can be as powerful as her dad - until she discovers a shocking secret. Now she must find a powerful magical weapon, or risk losing him for ever...
Keywords: Adventure; Fantasy; Juvenile Fiction